Integrating appraisal theory with possible selves in understanding university EFL writing. (November 2018) - McKinley, Jim
Abstract: This article explores how the taxonomy of evaluative meanings supplied by Martin and White's (2005) appraisal framework might be deployed to linguistically operationalize an analysis inspired by Clark and Ivanič's (1997) 'possibilities for selfhood'. While these two 'frameworks' operate at different logical/conceptual levels (i.e. they are concerned with meaning making at very different levels of abstraction), the taxonomies can be connected to make the analysis of EFL writer identity more explicit. In SFL terms, the appraisal framework offers an account of meaning making potential at the (discourse) semantic level, while Clark and Ivanič's system of different selves operates at the level of context of situation/culture. That is, the 'possibilities of selfhood' is a taxonomy of social roles while the appraisal framework is a taxonomy of meanings. The theory was tested in a study that examined the experiences of sixteen EFL writers in a Japanese university learning English composition over a period of one year. The paper shows how the framework can be applied through a detailed analysis of one case in this study, serving as an impetus for further inquiry into providing EFL writing teachers and students with explicit metalanguage for the social construction of writerly selves. Highlights: An adapted framework for analyzing students' written texts for writer identity is proposed. The framework clarifies meaning-making resources for effective foreign language writing. Writer identities should be explicitly taught allowing students to meet task expectations.